Individual dietary diversity is strongly associated with stunting in infants and young children - Bunga Astria Paramashanti; Yhona Paratmanitya; Marsiswati Marsiswati (Jurnal Gizi Klinik Indonesia, 2017)
Background: The increased nutrient fulfillment is required for optimal growth and development during the first two years of life. Based on WHO, dietary diversity is one of core indicators for assessing diet quality and adequacy.Objective: This study aimed to understand the association between individual dietary diversity and stunting in infants and young children in Sedayu Subdistrict, Bantul District, Yogyakarta, Indonesia.Method: This study used cross-sectional design. It was conducted from February to March 2016 in Sedayu Subdistrict. Subjects were 189 infants and young children aged 6-23 months selected by probability proportional to size sampling technique. Individual dietary diversity was assessed by minimum dietary diversity with the consumption of 4 or more food groups of the total 7 food goups. Data were analyzed by using statistics descriptive, Chi-Square test, and multiple logistic regression.Results: Poor dietary diversity (OR=16,76; 95%CI: 6,77-41,51) was significantly related with stunting. Other factor associated with stunting was low birth weight (OR=5,12; 95%CI: 2,11-12,43). In addition, appropiate time of introducing complementary food (OR=0,32; 95%CI: 0,13-0,75) was a protective factor against stunting. Household economic status acted as an effect modifier and confounding factor between dietary diversity and stunting.Conclusion: Consumption of diverse diet at least 4 food groups reduced the risk of stunting in infants and young children. Efforts should be made to improve dietary diversity in complementary feeding practice.